Assay of Nelfinavir Mesylate in Pharmaceutical Formulations by Visible Spectrophotometry - Murali Mohan Rao, S.V.; Rama Subba Reddy, T.; Viplava Prasad, U.; Sastry, C.S.P. (Asian Journal of Chemistry, 2010)
Three simple and sensitive visible spectrophotometric methods (A-C) for the determination of nelfinavir mesylate (NEL) in bulk and pharmaceutical formulations are described. Methods A and B are based on the formation of ion-association complexes between NEL and wool-fast blue BL (WFB BL, λmax 590 nm) or Tropaeolen 000 (TP 000, λmax 480 nm). Method C is based on the formation of diazo coupling product of NEL with diazotized p-nitroaniline (DPNA, λmax 480 nm). Regression analysis of Beer's law plots showed good concentration ranges (0.5-5.0, 1.9-20 and 2.0-25) μg/mL for methods A, B and C respectively.